Exploring the Synergy of Global Markets and Digital Innovation in Business Growth Using SmartPLS - Pambudi, Ari; Wilson, Oliver; Zanubiya, Jihan (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
In the context of Indonesia emerging markets, this study evaluates the impact of international markets and digital technology on business innovation, with entrepreneurial orientation acting as a mediator. A descriptive survey methodology using a standard questionnaire was applied to service businesses, and data were analyzed using structural equation modeling with SmartPLS 4.0. The results show a positive relationship between engagement in international markets and the adoption of digital technology, which enhances business innovation. This relationship is further strengthened by a proactive and risk taking entrepreneurial orientation. The study concludes that the strategic integration of global markets and digital technology, driven by entrepreneurship, is crucial for sustainable innovation in Indonesia. The study provides insights for policymakers and practitioners on how to leverage technology and international markets in their innovation strategies. For example, businesses in Indonesia can integrate digital payment systems and customer relationship management tools to streamline cross border transactions, ensuring both operational efficiency and innovative service delivery.